If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 6y = -70 Solving 8x + 6y = -70 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6y' to each side of the equation. 8x + 6y + -6y = -70 + -6y Combine like terms: 6y + -6y = 0 8x + 0 = -70 + -6y 8x = -70 + -6y Divide each side by '8'. x = -8.75 + -0.75y Simplifying x = -8.75 + -0.75y
| 2(3x-1)=3x+13 | | 9x+2=5x+19 | | 2x+54=5x | | 6x-20=-2 | | 2x-14=-3 | | x+2y=7 | | 2-x=4x-7 | | 4x-3=2x-3 | | 12(15x-11)+20-17(10x+30)=-40x+9(12x+4)-16 | | 2x+1=7-x | | 5x+8=3x+3 | | 5x+15=65 | | 5(x-4)=2x-11 | | 5x+15=75 | | .5(y+12)=-2.5y-8 | | 32+0.2c=1 | | 3n-5=19 | | 3x+11x+19= | | -2x-3y+4z=4 | | 50-5x=16+4x | | 40+2x=16+4x | | 10x+60=120+8x | | 8(x-3)=7x | | x+4y=21 | | 4(x+10)+10=9x | | 5(x-3)+3x=12x | | 6(x-10)=2x | | 10(x-8)(5x+1)=0 | | (x-7)(5x+2)=0 | | (x-9)(x+3)=0 | | 4x(x+2)=0 | | 4(x+9)=16x-10x |